Regional public bus transport – regress, reforms, recommendations - Wolański, Michał; Mrozowski, Wiktor; Pieróg, Mateusz (Journal of Public Governance, 2016)
Regional public bus (coach) services in Poland have faced serious challenges in recent years. A large part of the transport system is preserved solely by means of the public refunding of reduced fares. The new Act on mass public transport aims to improve the situation by encouraging local authorities to take responsibility for regional transport systems. The aim of this paper is to evaluate regulations implemented, to formulate recommendations leading to an improved transport system based around the new legislation, and to prepare long-term recommendations by which the legislative process might be streamlined in future. The available literature and detailed analysis of amended refunding regulations entering into force on 1/01/2017 make it clear that the further operation of regional transport systems outside urban areas is threatened by the reluctance of local governments to contract and finance public services. However, the authors feel a better-quality and more cost-effective regional transport system is achievable, provided the route network is planned appropriately, and integrates both regular routes and school services, with monthly tickets purchased wholesale. In the long run, more profound change, including new legislation, are essential, with a view to the entire system by which rural public transport in Poland is financed and organised being redefined.